Factors Associated with Anemia in A sample of Pregnant Women Attending Primary Health Centers - Zeidan, muna (Iraqi National Journal of Nursing Specialties, 2013)
Objective (s): To determine proportion of anemia among sample of Pregnant women. To identify factors associated with the anemia (Maternal age, maternal education, gestational age, parity, gravidity, birth interval, smoking, taking iron supplements and dietary habits). Methodology: A cross-sectional study conducted at Al- washash & Bab-almoadham primary health care centers. The sample was selected by (non-probability convenient sampling) and sample size was (550). The study started from 1st March 2011 to 30th of March 2012. The data was collected by direct interview using special questionnaire to obtained socio-demographic information. Results: the result shows that mean age of the subjects was 26.5± 7.5 years, 85.8% were housewives; about (45.6%) of pregnant women in the sample were anemic. About (52.2%) of the pregnant women with anemia were mainly at 3rd trimester of their pregnancy. Analysis of results by chi-square test show that (Maternal age, maternal education, gestational age, parity, gravidity, birth interval, smoking, taking iron supplements and dietary habits) were significant factors associated with anemia. Recommendations: the present study recommends that priority should be given to provide education and other social services in on the prevention of pregnancy-induced anemia.